Activation of spinal N-methyl-d-aspartate or neurokinin receptors induces long-term potentiation of spinal C-fibre-evoked potentials in spinalized rats - Liu, Xianguo; Sandkühler, Jürgen (Neuroscience, 1998)
The use-dependent increase in synaptic strength between primary afferent C-fibres and second-order neurons in superficial spinal dorsal horn may be an important cellular mechanism underlying central hyperalgesia. This long-term potentiation can be blocked by antagonists of the N-methyl-d-aspartate subtype of glutamate receptor, the neurokinin 1 or the neurokinin 2 receptor. We have tested here whether activation of these receptors by superfusion of the spinal cord with corresponding agonists in the absence of presynaptic activity is sufficient to induce long-term potentiation. In urethane anaesthetized rats C-fibre-evoked field potentials were elicited in superficial laminae of lumbar spinal cord by electrical stimulation of the sciatic nerve. In rats with intact spinal cord, controlled superfusion of the spinal cord at recording segments for 60min with N-methyl-d-aspartate, substance P or neurokinin A never induced long-term potentiation. Spinal superfusion with a mixture of N-methyl-d-aspartate, substance P and neurokinin A also failed to induce long-term potentiation in four rats tested. In spinalized rats, however, long-term potentiation was induced by either N-methyl-d-aspartate (at 10μM, to 173±16% of control) substance P (at 10μM, to 176±13% of control) or by neurokinin A (at 1μM, to 198±.20% of control). The induction of long-term potentiation by N-methyl-d-aspartate, substance P or neurokinin A was blocked by intravenous application of the receptor antagonists dizocilpine maleate (0.5mg/kg), RP67580 (2mg/kg) or SR48968 (0.2mg/kg), respectively. Thus, activation of N-methyl-d-aspartate or neurokinin receptors may induce long-lasting plastic changes in synaptic transmission in afferent C-fibres and this effect may be prevented by tonic descending inhibition.
Gesehen am 04.05.2021